2015
DOI: 10.1021/acs.analchem.5b01705
|View full text |Cite
|
Sign up to set email alerts
|

Comparison of Atmospheric Pressure Ionization Gas Chromatography-Triple Quadrupole Mass Spectrometry to Traditional High-Resolution Mass Spectrometry for the Identification and Quantification of Halogenated Dioxins and Furans

Abstract: The goal of this study was to qualify gas chromatography coupled to atmospheric pressure ionization tandem mass spectrometry (APGC-MS/MS) as a reliable and valid technique for analysis of halogenated dioxins and furans that could be used in place of more traditional gas chromatography coupled to high-resolution mass spectrometry (GC-HRMS) analysis. A direct comparison of the two instrumental techniques was performed. APGC-MS/MS system sensitivity was demonstrated to be on the single femtogram level. The APGC-M… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
23
0
1

Year Published

2015
2015
2020
2020

Publication Types

Select...
7
1

Relationship

3
5

Authors

Journals

citations
Cited by 41 publications
(25 citation statements)
references
References 18 publications
1
23
0
1
Order By: Relevance
“…Samples were analyzed using a Waters Xevo G2-XS qTOF fitted with a 15 m x 0.25 mm x 0.1 µm DB-5 HT (5% phenyl) GC column. This was connected to a 0.8 m x 1.8 mm sulfinert treated MXT tubing in the transfer line, following guidance from Organtini et al 19 The injector temperature was set at 280 ⁰C, and transfer line at 330⁰C. The initial oven temperature was set at 110 ⁰C with a ramp of 40⁰C a minute to 200 ⁰C, 10 ⁰C a minute to 280 ⁰C and 30 ⁰C a minute to 330 ⁰C and held for 5 minutes, resulting in a total run time of 17.92 minutes.…”
mentioning
confidence: 99%
“…Samples were analyzed using a Waters Xevo G2-XS qTOF fitted with a 15 m x 0.25 mm x 0.1 µm DB-5 HT (5% phenyl) GC column. This was connected to a 0.8 m x 1.8 mm sulfinert treated MXT tubing in the transfer line, following guidance from Organtini et al 19 The injector temperature was set at 280 ⁰C, and transfer line at 330⁰C. The initial oven temperature was set at 110 ⁰C with a ramp of 40⁰C a minute to 200 ⁰C, 10 ⁰C a minute to 280 ⁰C and 30 ⁰C a minute to 330 ⁰C and held for 5 minutes, resulting in a total run time of 17.92 minutes.…”
mentioning
confidence: 99%
“…An interlaboratory study was previously performed in which the APGC-MS/MS instrument was directly compared to a magnetic sector high resolution mass spectrometer. 20 The APGC-MS/MS system demonstrated equivalent, or better, performance than the GC-HRMS system for chlorinated dibenzo-p-dioxin and dibenzofuran analysis. It also demonstrated increased sensitivity with the ability to significantly expand upon the dioxin analysis methods that only monitor for 17 polychlorinated congeners without sacrificing sensitivity.…”
Section: ■ Experimental Sectionmentioning
confidence: 96%
“…The TQ-S used in this experiment was used in a previous study by Organtini et al, comparing its performance to a GC-HRMS for dioxin analysis in fish and soil samples. 33 A similar study was conducted by van Bavel et al, which utilized 4 different TQ-S instruments and compared them to a GC-HRMS. 34 The current study found that the MDL for the TQ-S shows an average improvement of 2-fold over GC-HRMS with a maximum improvement of 3-fold for 1,2,3,7,8-PeCDD.…”
Section: Target Specific Analysismentioning
confidence: 97%